SALIVARY HUMORAL AND CYTOKINE IMMUNE INDICATORS IN CHILDREN WITH RECURRENT HERPETIC STOMATITIS, INCLUDING THOSE WITH CONCURRENT ALLERGIC DISEASES - Razikova Dilnoza Kadirovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Recurrent herpetic stomatitis (RHS) is a common pediatric infection caused by herpes simplex virus type 1, often associated with impaired mucosal immunity. When accompanied by allergic diseases, the severity of immune dysregulation may increase. This study investigated local humoral and cytokine immunity in children with RHS, both isolated and combined with allergic conditions. Methods: A total of 120 children aged 1–7 years were examined and divided into three groups: healthy controls (n=40), RHS without allergy (n=40), and RHS with allergy (n=40). Saliva samples were collected and analyzed for secretory IgA (sIgA), lysozyme, total IgA, IgM, IgG, IgE, as well as cytokines IL-6 and IL-10 using ELISA. Statistical analysis was performed to compare groups. Results: Children with RHS demonstrated a significant decrease in sIgA and lysozyme levels compared with controls, which was more pronounced in allergic patients (sIgA: 207.17 vs. 90.57 µg/mL; lysozyme: 159.76 vs. 76.71 µg/mL, p